2015
DOI: 10.1017/s0007114514004425
|View full text |Cite
|
Sign up to set email alerts
|

Glycaemic index and glycaemic load of selected popular foods consumed in Southeast Asia

Abstract: The objective of the present study was to determine the glycaemic index (GI) and glycaemic load (GL) values of standard portion sizes of Southeast Asian traditional foods. A total of fifteen popular Southeast Asian foods were evaluated. Of these foods, three were soft drinks, while the other twelve were solid foods commonly consumed in this region. In total, forty-seven healthy participants (eighteen males and twenty-nine females) volunteered to consume either glucose at least twice or one of the fifteen test … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 32 publications
(42 reference statements)
1
17
0
Order By: Relevance
“…The low glucose peak displayed by June plum and cucumber may lead to low demand for insulin secretion from pancreatic Beta-cells. These are promising results in terms of their recommendation to patients with diabetes as well as healthy subjects [3,6,19,20].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The low glucose peak displayed by June plum and cucumber may lead to low demand for insulin secretion from pancreatic Beta-cells. These are promising results in terms of their recommendation to patients with diabetes as well as healthy subjects [3,6,19,20].…”
Section: Discussionmentioning
confidence: 93%
“…The higher the GL of the food, the greater the rise of blood glucose and insulin levels. Long-term consumption of a high GL diet has been linked with increased risk of type 2 diabetes and related complications [4,8,12,[14][15][16][17] Research has shown that consuming low GI foods is a possible inexpensive dietary alternative in the management of diabetes [3,6,[18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…It is the first study to corroborate that by constructing a 24 h low GI diet using local foods described as low GI, that these low GI Asian foods are capable of reducing 24 h glycaemic response and glycaemic variability and simultaneously promote fat oxidation over carbohydrate oxidation. The study expanded on previous work from our group on glycaemic index of single Asian foods on glucose response [13] and now included the measurement of substrate oxidation using a whole body calorimeter. The results are in line with the hypothesis that high GI foods result in hyperinsulinemia which in turn leads to less fat oxidation and possibly increased fat deposition [17, 37].…”
Section: Discussionmentioning
confidence: 99%
“…With the lack of published GI values of local foods, Henry and colleagues among others conducted several studies which determined the GI values of local commonly consumed foods, that were not previously tested [13]. The GI values of local foods provide valuable information to consumers, researchers and dietitians to optimize food choice for glycaemic control.…”
Section: Introductionmentioning
confidence: 99%
“…Co‐ingestion of both soymilk and dairy milk with bread significantly lowered blood glucose response, with soymilk eliciting a higher insulin response (Sun et al., ). Free amino acids had greater efficacy in limiting postprandial blood glucose than whole proteins when co‐ingested with carbohydrates (Soong, Lim, et al., ; Sun, Tan, et al., ).…”
Section: Reducing the Glycemic Impact Of Mealsmentioning
confidence: 99%